MiR-183-5p suppressed the invasion and migration of HTR-8/SVneo trophoblast cells partly via targeting MMP-9 in preeclampsia. Issue 6 (4th June 2020) - Suo, Mingli; Sun, Yanfei; Yang, Hailan; Ji, Jing; He, Yinfang; Dong, Liyuan; Wang, Yuxian; Zhang, Yanli; Zhang, Yingan; Hao, Min
Abstract: Preeclampsia (PE), a common obstetrical disorder, is characterized by impaired migration and invasion abilities of trophoblastic cells. MicroRNA-183-5p (miR-183) was reported to regulate cell migration and invasion in various types of human cancers; however, its role in the pathogenesis of PE remains elusive. Herein, we investigated the role of miR-183 in HTR-8/SVneo trophoblast cells invasion and migration and explored the underlying mechanism. Our results showed that miR-183 was significantly up-regulated in placental tissues from pregnant women compared with that in normal pregnant women. Overexpression of miR-183 inhibited proliferation, migration and invasion, as well as induced apoptosis in HTR-8/SVneo cells. Otherwise, down-regulation of miR-183 achieved the opposite effects. Bioinformatics prediction and luciferase reporter assay confirmed that matrix metalloproteinase-9 (MMP-9) is a target of miR-183. In addition, MMP-9 expression was significantly down-regulated, and inversely correlated with the miR-183 level in placental tissues from pregnant women with severe PE. Down-regulation of MMP-9 suppressed the trophoblast cell invasion and migration, whereas overexpression of MMP-9 promoted cell invasion and migration in HTR-8/SVneo cells. More importantly, up-regulation of MMP-9 reversed the inhibitory effects of miR-183 on cell invasion and migration in trophoblast cells. Collectively, our findings suggested that miR-183 may play critical roles in the pathogenesis of PE and serve as a potential biomarker for severe PE.